Pneumaturia signaling a fistula between the rectum anastomosis and seminal vesicle as a complication after transanal endorectal pull-through operation for Hirschsprung's disease. A method of repair - Christina Granéli; Pernilla Stenström; Anna Börjesson; Antoni Zawadzki; Hans Frederiksen; Magnus Anderberg; Einar Arnbjörnsson (Elsevier, 2014)
A 2-year-old boy underwent an uneventful transanal endorectal pull-through for Hirschsprung's disease. Postoperatively he suffered from pneumaturia which prompted surgical evaluation. He was found to have a rectum to seminal vesicle fistula. He was re-operated closing the fistula through an anterior transperineal approach with a successful operative outcome.